OPTIMALISASI PENGAPLIKASIAN SISTEM AKUNTANSI PADA CV KONVEKSI DENGAN METODE PEMBIAYAAN YANG EFEKTIF - Hasanudin , Surya; Yulia , Yuyun; Purwanti, Purwanti (Komunitas Manajemen Kompetitif, 2025)
The success of a business, including in the garment industry, is greatly influenced by an efficient and effective accounting system. CV Konveksi, as a company in the clothing production sector, requires an accounting system capable of recording, managing, and analyzing financial reports effectively to improve transparency and accountability. In addition, the financing method used in the company is also important to support operational continuity and strategic decision-making. This study aims to improve the use of the accounting system at CV Konveksi by implementing an appropriate funding method. It is hoped that this will increase efficiency in the company's financial management. The approach used in this study is a qualitative descriptive method through a case study at CV Konveksi which experienced difficulties in implementing the accounting system and in selecting a funding method. Data were obtained through direct observation, interviews with management, and literature studies related to accounting systems and financing methods relevant to small and medium enterprises (MSMEs). The analysis was conducted to identify existing problems in the implementation of the accounting system and financing methods, and provide strategic recommendations to optimize both. The findings indicate that the accounting system used at CV Konveksi still has several weaknesses, such as manual transaction recording, minimal use of accounting software, and a lack of employee understanding of the importance of systematic financial recording. This results in delays in financial reporting, errors in transaction recording, and difficulties in accurately identifying the company's financial condition. To address these issues, it is recommended to use a digital-based accounting system that can facilitate direct financial recording, management, and analysis. Furthermore, the financing method adopted by CV Konveksi also needs to be optimized for greater effectiveness. Keywords — Accounting system, financing method, garment industry, MSMEs, financial efficiency